Investigating the increase of violent speech in Incel communities with human-guided GPT-4 prompt iteration - Matter, Daniel; Schirmer, Miriam; Grinberg, Nir; Pfeffer, Jürgen (Frontiers in Social Psychology, 2024)
This study investigates the prevalence of violent language on incels.is. It evaluates GPT models (GPT-3.5 and GPT-4) for content analysis in social sciences, focusing on the impact of varying prompts and batch sizes on coding quality for the detection of violent speech. We scraped over 6.9M posts from incels.is and categorized a random sample into non-violent, explicitly violent, and implicitly violent content. Two human coders annotated 3, 028 posts, which we used to tune and evaluate GPT-3.5 and GPT-4 models across different prompts and batch sizes regarding coding reliability. The best-performing GPT-4 model annotated an additional 45, 611 posts for further analysis. We find that 21.91% of the posts on the forum contain some form of violent language. Within the overall forum, 18.12% of posts include explicit violence, while 3.79% feature implicit violence. Our results show a significant rise in violent speech on incels.is, both at the community and individual level. This trend is particularly pronounced among users with an active posting behavior that lasts for several hours up to one month. While the use of targeted violent language decreases, general violent language increases. Additionally, mentions of self-harm decline, especially for users who have been active on the site for over 2.5 years. We find substantial agreement between both human coders (κ = 0.65), while the best GPT-4 model yields good agreement with both human coders (κ = 0.54 for Human A and κ = 0.62 for Human B). Overall, this research offers effective ways to pinpoint violent language on a large scale, helping with content moderation and facilitating further research into causal mechanisms and potential mitigations of violent expression and online radicalization in communities like incels.is.